2010
DOI: 10.1177/1524838010390708
|View full text |Cite
|
Sign up to set email alerts
|

College- or University-Based Sexual Assault Prevention Programs: A Review of Program Outcomes, Characteristics, and Recommendations

Abstract: This article examines literature reviews of research articles and dissertations focused on the effectiveness of college- or university-based sexual violence prevention programs. Literature reviews were eligible for inclusion in this article if they examined empirical published peer-reviewed research articles or dissertation research that reported original data; focused on examining the effectiveness of programs that were developed to reduce sexual violence that occurred in college or university settings; offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
199
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(210 citation statements)
references
References 60 publications
6
199
0
5
Order By: Relevance
“…Second, some of the FYCEP teams may have returned to the issue of defining "sexual assault" and "consent" during enrichment sessions, raising the group mean. This possibility is consistent with what Vladutiu et al (2011) reported is effective in reducing rape myth acceptance. Although these students had higher confidence levels, their knowledge was not better than the average student.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Second, some of the FYCEP teams may have returned to the issue of defining "sexual assault" and "consent" during enrichment sessions, raising the group mean. This possibility is consistent with what Vladutiu et al (2011) reported is effective in reducing rape myth acceptance. Although these students had higher confidence levels, their knowledge was not better than the average student.…”
Section: Discussionsupporting
confidence: 93%
“…First, students who discussed the content of the lecture with a group of peers and a leader with whom they would have a long-term relationship may have had deeper conversations and thus felt more confident in their understanding. This possibility is consistent with previous findings that small group discussions lead to greater reduction in rape myth acceptance (Vladutiu et al, 2011). Second, some of the FYCEP teams may have returned to the issue of defining "sexual assault" and "consent" during enrichment sessions, raising the group mean.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Facilitators (Table 3) were classified based on recommendations for effectiveness of (a) programs for prevention of college sexual violence (Vladutiu, Martin, & Macy, 2011), including the type of audience, facilitator, format, and program; and (b) public health intervention programs in general, including collaboration and availability of resources (including technical assistance) (Weiss, Lillefjell, & Magnus, 2016). For quality improvement, the challenges and concerns attributed to the program were also captured (Table 3).…”
Section: Likelihood Of Committing Rapementioning
confidence: 99%